Kampong Cooperative Development And Sustainability From MIZAN Principles: A Case Study At Negeri Sembilan - Ummi Salwa Ahmad Bustamam; Nuradli Ridzwan Shah Mohd Dali; Nur Ainna Ramli; Nur Shuhada Kamarudin; Khatijah Othman; Zulhamizan Ismail; Asmaddy Haris (Co-operative Institute of Malaysia, 2024)
Malaysian Journal of Co-operative Studies Volume 15 2019 29-46